IMPLIKASI PRINSIP BELAJAR AKTIF BAGI GURU DAN PESERTA DIDIK DALAM PEMBELAJARAN PENDIDIKAN AGAMA KATOLIK - Reresi, Marsianus (LOGOS: JURNAL PENDIDIKAN KEAGAMAAN KATOLIK, 2022)
This research is a library research that aims to analyze the implications of active learning principles forteachers and students in learning Catholic Religious Education. The research method used is descriptive research with library research studies (library research). In this study, the author usesdescriptive research with more emphasis on the strength of the analysis of available sources and data by relying on theories and concepts to be interpreted and described which leads to the focus of thediscussion. The results of the study found that the implications of the principle of active learning in PAK learning require teachers to design learning that activates students, frees students from excessive dependence on teachers, and teachers need to assess learning processes and outcomes. Likewise,students are required to actively form knowledge about themselves, the Person of Jesus Christ, theChurch and Society. Students need to actively build their attitudes and skills in implementing their faith knowledge. The atmosphere of active PAK learning becomes more lively when there is activestructured interaction between students and learning resources Keywords: Active Learning Principles, PAK